A miniaturized spectrometer radiometer based on MMIC technology for tropospheric water vapor profiling - Padmanabhan, Sharmila, author; Reising, Steven C., author; Iturbide-Sanchez, Flavio, author; IEEE, publisher (Colorado State University. Libraries, 2007)
The fabrication of a miniaturized ground-based water vapor profiling radiometer demonstrates the capability of monolithic microwave and millimeter-wave integrated circuit technology to reduce the mass and volume of microwave remote sensing instrumentation and to reduce substantially the necessary operational power consumption and size of the radiofrequency and intermediate-frequency sections. Since those sections comprise much of the mass and volume of current microwave receivers, the fabrication of this system represents an important contribution to the design of microwave radiometers. This miniaturized radiometer implementation is particularly well suited to benefit from the cost savings associated with mass production. The small size of the radiometer (24 × 18 × 16 cm) reduces the power required by the temperature control system and allows a rapid warm-up to the temperature set point as well as maintenance of a highly stable internal temperature. Exhibiting very similar statistical properties, the four channels of the radiometer have measured Allan times of greater than 40 s. Measurement results demonstrate that the instrument achieves a sensitivity of better than 0.2 K for 3 s of integration time. Preliminary comparisons of measured brightness temperatures with simulation results based on radiosonde data show good agreement, which are consistent with previously reported results.
Keywords: monolithic microwave and millimeter-wave integrated circuits (MMICs); microwave radiometry; humidity measurement; atmospheric measurements; multichip modules (MCMs); remote sensing